2012
DOI: 10.1021/es3010656
|View full text |Cite
|
Sign up to set email alerts
|

New Halogenated Disinfection Byproducts in Swimming Pool Water and Their Permeability across Skin

Abstract: Chlorine is widely used for disinfecting public swimming pool water. The disinfectant chlorine, protecting swimmers from pathogenic infection in swimming, may be responsible for some adverse effects on swimmers' skin and health. In this study, numerous new halogenated disinfection byproducts (DBPs) in chlorinated pool water were detected with a powerful precursor ion scan method using electrospray ionization triple quadrupole mass spectrometry, with or without preseparation with ultra performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…S1, the concentrations of these compounds detected in indoor pools (mean 144 ng L −1 ) were roughly 20-fold higher than those in outdoor pools (mean 6.78 ng L −1 ). This result is consistent with previous reports that concentrations of DBPs in indoor pools were higher than those in outdoor pools (Xiao et al 2012;Yeh et al 2014). Compared to the indoor pools, opening times for outdoor pools are usually short.…”
Section: Comparison Of Different Poolssupporting
confidence: 94%
See 1 more Smart Citation
“…S1, the concentrations of these compounds detected in indoor pools (mean 144 ng L −1 ) were roughly 20-fold higher than those in outdoor pools (mean 6.78 ng L −1 ). This result is consistent with previous reports that concentrations of DBPs in indoor pools were higher than those in outdoor pools (Xiao et al 2012;Yeh et al 2014). Compared to the indoor pools, opening times for outdoor pools are usually short.…”
Section: Comparison Of Different Poolssupporting
confidence: 94%
“…However, growing studies suggest that exposure to the water in swimming pools may result in a variety of health risks, such as increased asthma and allergy, which are associated with microbial and chemical hazards (Bernard et al 2006;Pasquarella et al 2013Pasquarella et al , 2014. Recent studies have raised concerns on adverse health impacts associated with application of personal care products and disinfection by-products (DBPs) formed in swimming pools (Chowdhury et al 2014;Kim et al 2002;Xiao et al 2012). The presence of pollutants originating from the application of preservatives has been reported in swimming pools (Teo et al 2015;Terasaki and Makino 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The combined treatments such as ozone and UV or salt electrolysis produced a lower probability of perceived health problems and greater satisfaction (Fernandez-Luna et al 2015). Further, Xiao et al (2012) reported DBP formation from human skin at a dose of 400 μg/L Br − and 2 mg/L Cl 2 . Disinfection practice can play an important role on exposure to DBPs in a swimming pool.…”
Section: Reducing Dbp Exposurementioning
confidence: 99%
“…Emerging DBPs are being identified in pool water (Pan and Zhang 2013;Xiao et al 2012). The personal care and pharmaceutical products can be present in swimming pools, which can play an important role in the formation and distribution of emerging DBPs.…”
Section: Role Of Other Dbpsmentioning
confidence: 99%
“…Despite that the best known and most intensively investigated THMs remained at relatively low concentrations (18-133 μg/L) in swimming pool water (Fantuzzi et al, 2001;Chu and Nieuwenhuijsen, 2002), surveys around the world have reported that the THAA concentrations in swimming pools could be higher than 6800 μg/L, which is several orders of magnitude higher than the abovementioned MCL (Tang, 2011;Simard et al, 2013;Wang et al, 2014;Chowdhury et al, 2014;Teo et al, 2015). As these DBPs can be taken up through dermal absorption (Xiao et al, 2012), ingestion, and inhalation (Lee et al, 2009), increasing attention is being focused on the potential health risks associated with exposure to such high levels of DBPs for pool users and attendants at indoor and outdoor pools Liviac et al, 2010;Richardson et al, 2010). It is therefore highly desirable to develop technologies on effective control of HAAs in swimming pool water.…”
Section: Introductionmentioning
confidence: 99%